2022
DOI: 10.1080/14786419.2022.2101053
|View full text |Cite
|
Sign up to set email alerts
|

Two new monoterpene esters from the pericarps of Alpinia zerumbet

Abstract: Two new monoterpene esters (1 and 2) and four known compounds (3-6) were isolated from the pericarps of Alpinia zerumbet. Their structures were elucidated by extensive spectroscopic analyses and their anti-inflammatory activity was evaluated by monitoring their inhibitory effects on the interleukin-1β-induced production of nitric oxide in primary cultured rat hepatocytes. The new compound 1 and cardamonin 3 showed inhibitory activities with IC50 values of 17.6 ± 1.1 and 10.2 ± 1.3 µM, respectively, which are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…In total, 28 previous studies [ 15 , 19 , 20 , 28 , 56 , 59 , 69 , 78 , 84 , 93 , 98 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ] show that more than 100 compounds have been isolated from the leaves [ 15 , 56 , 69 , 110 , 111 , 113 ], rhizomes [ 19 , 28 , 56 , 78 , 84 , 104 , 105 , 106 , 109 , 114 , 115 , 116 , 118 , 119 , 120 ], fruits [ 93 ], pericarps [ 59 , 107 ...…”
Section: Phytochemicalsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 28 previous studies [ 15 , 19 , 20 , 28 , 56 , 59 , 69 , 78 , 84 , 93 , 98 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ] show that more than 100 compounds have been isolated from the leaves [ 15 , 56 , 69 , 110 , 111 , 113 ], rhizomes [ 19 , 28 , 56 , 78 , 84 , 104 , 105 , 106 , 109 , 114 , 115 , 116 , 118 , 119 , 120 ], fruits [ 93 ], pericarps [ 59 , 107 ...…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Xuan and Teschke [ 122 ] suggested that 7,8-dihydro-5,6-dehydrokawain ( 2 ) was first isolated 40 years ago by Pooter et al However, Kimura et al [ 104 ] isolated 5,6-dehydrokawain ( 1 ) and 7,8-dihydro-5,6-dehydrokawain ( 2 ) from the rhizomes of A. zerumbet in 1966. Thereafter, 5,6-dehydrokawain ( 1 ) was isolated from the leaves [ 15 , 56 , 69 ], rhizomes [ 19 , 105 , 106 , 109 ], fruits [ 93 ], pericarps [ 59 , 107 , 108 ], and flowers [ 98 ] of the plant, and 7,8-dihydro-5,6-dehydrokawain ( 2 ) was isolated from its leaves [ 15 , 56 , 69 , 110 ], rhizomes [ 19 , 105 , 106 ], fruits [ 93 ], and pericarps [ 59 , 107 , 108 ].…”
Section: Phytochemicalsmentioning
confidence: 99%
See 3 more Smart Citations